Digitalization As a Factor of Innovative Development - Sherbek Naimovich Khayitov (Genius Publishing Group, 2021)
The relevance of the article topic is determined by the need to develop theoretical guidelines to increase the sustainability and efficiency of innovation-based industrial development, i.e. based on the knowledge economy. This is especially important in the context of limited economic resources and insufficient use of scientific and technological advances.
Keywords: Macroeconomic structure; world economy; country's industry; innovative activities